2019
DOI: 10.1016/j.jid.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis Herpetiformis and Celiac Disease Increase the Risk of Bullous Pemphigoid

Abstract: Bullous pemphigoid (BP) and dermatitis herpetiformis (DH) are autoimmune bullous skin diseases. DH has been described to evolve into BP and the two diseases can have overlapping clinical appearances and diagnostic findings, but the association between DH and BP has not previously been studied in a large population. To evaluate DH and celiac disease as risk factors for BP, we conducted a retrospective case-control study of patients with BP and matched controls with basal cell carcinoma diagnosed in Finland betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 60 publications
0
13
0
2
Order By: Relevance
“…This result may have been related to patient demographics. The mean age of DH patients was on average 20 years lower than that recently reported in patients with a BP diagnosis preceded by DH (68.8 years) (5). Gluten-induced autoimmunity has a much earlier onset than BP, and in Finland patients with DH or CD have a high level of adherence to the recommended gluten-free diet (38).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This result may have been related to patient demographics. The mean age of DH patients was on average 20 years lower than that recently reported in patients with a BP diagnosis preceded by DH (68.8 years) (5). Gluten-induced autoimmunity has a much earlier onset than BP, and in Finland patients with DH or CD have a high level of adherence to the recommended gluten-free diet (38).…”
Section: Discussionmentioning
confidence: 66%
“…Numerous studies have demonstrated that the risk of developing BP is significantly elevated in individuals who have neurodegenerative diseases or use dipeptidyl peptidase-4 inhibitors (gliptins) to treat diabetes ( 24 27 ). A preceding diagnosis of another itching and blistering disease, DH, is associated with an even greater risk elevation ( 5 ). The molecular mechanisms by which different risk factors induce the immune system to act against BP180 are unknown, although neuroinflammation leading to the failure of self-tolerance against BP180, immunological changes caused by gliptins and epitope spreading have all been suggested ( 16 , 17 , 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like CD, DH has been found to be associated with several autoimmune disorders, including type I diabetes mellitus, autoimmune thyroid diseases, and connective tissue diseases, such as Sjögren syndrome (24). Of interest is also the reported association between DH and bullous pemphigoid (BP), a subepidermal autoimmune blistering disease characterized by autoimmunity against the hemidesmosomal antigens BP180 and BP230 (26, 27). Accordingly, in a retrospective case-control study, diagnosis of DH was found to increase of 22 folds the risk of BP, compared to only a 2-fold higher risk of developing BP amongst coeliac patients.…”
Section: The Epidemiology Of Dermatitis Herpetiformis: a (Rare) Diseamentioning
confidence: 99%
“…Another association with BP might be dermatitis herpetiformis (DH). Patients with DH have a 22-fold increased risk to develop subsequent BP, with a mean time of 3 years in between diagnoses of DH and BP (Varpuluoma et al, 2019). However, in our experience, DH followed by BP is still a very unusual event.…”
Section: Clinical Studies and Mechanisms Of Therapy In Pemphigusmentioning
confidence: 55%